The bidirectional regulatory mechanism of gut microbiota metabolites on myocardial injury in heart failure from the perspective of the gut-heart axis: a review - Guo, Siyi; Zhang, Wenhui; Cui, Xiaoxue; Yin, Bao (Frontiers in Microbiology, 2025)
Dysregulation of gut microbiota-derived metabolites is closely associated with heart failure (HF). However, current research lacks a comprehensive integration of the gut-heart axis regulatory mechanisms, especially regarding an in-depth analysis of the dual roles of key metabolites. This review systematically examines recent advances in the regulation of HF by gut microbiota metabolites, focusing on their bidirectional regulatory mechanisms. Key findings show that HF patients exhibit specific microbial community changes, intestinal barrier damage, and microbiota aging. Toxic metabolites [e.g., trimethylamine N-oxide (TMAO), phenylacetylglutamine (PAGln), and lipopolysaccharide (LPS)] exacerbate HF through mechanisms such as inflammatory activation, oxidative stress, and fibrosis promotion. In contrast, protective metabolites [e.g., short-chain fatty acids (SCFAs), bile acid (BA), hydrogen sulfide (H₂S), and indole derivatives] offer compensatory protection through opposing pathways, including anti-inflammatory effects, antioxidant activity, and maintenance of metabolic homeostasis. Some metabolites demonstrate temporal bidirectional regulation within the same pathological process, with their dual roles dynamically modulated by factors such as dose, timing, host status, and disease stage. Future research should prioritize investigating the metabolite-host interaction network, developing precision intervention strategies, and facilitating the clinical translation of gut-heart axis insights for the precise prevention and treatment of HF.